3(2y-15)=-(y-6)

Simple and best practice solution for 3(2y-15)=-(y-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2y-15)=-(y-6) equation:


Simplifying
3(2y + -15) = -1(y + -6)

Reorder the terms:
3(-15 + 2y) = -1(y + -6)
(-15 * 3 + 2y * 3) = -1(y + -6)
(-45 + 6y) = -1(y + -6)

Reorder the terms:
-45 + 6y = -1(-6 + y)
-45 + 6y = (-6 * -1 + y * -1)
-45 + 6y = (6 + -1y)

Solving
-45 + 6y = 6 + -1y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add 'y' to each side of the equation.
-45 + 6y + y = 6 + -1y + y

Combine like terms: 6y + y = 7y
-45 + 7y = 6 + -1y + y

Combine like terms: -1y + y = 0
-45 + 7y = 6 + 0
-45 + 7y = 6

Add '45' to each side of the equation.
-45 + 45 + 7y = 6 + 45

Combine like terms: -45 + 45 = 0
0 + 7y = 6 + 45
7y = 6 + 45

Combine like terms: 6 + 45 = 51
7y = 51

Divide each side by '7'.
y = 7.285714286

Simplifying
y = 7.285714286

See similar equations:

| 690+1= | | 20logk=14 | | 8-3m=35 | | 9-m=-3 | | X+Y+Z=36 | | x+9=4(5+2) | | 0.4y-6.7+y-0.3-26y= | | 0.4y-6.7+-0.3-26y= | | 6.4c=0.8 | | 6cos^2(x)+7sin(x)-1=0 | | 6x+10+3sinx=0 | | 7p-14=7(p-2) | | 15/250=1/x | | 10-5h=5(-h+2) | | 5x+24=8x+27 | | 15/250=x/15 | | 10c=5(2c+13) | | -15w-9=3(-5w-3) | | 20+r=7r-11r-10 | | -15+m=8(-3m+20) | | (1/4x)-(3/x)=-9/8 | | 15y+5y-9=20y-9 | | 6y+2t= | | 5-4-5z=-5z+1 | | 2(11u+12)=18u-20 | | -19+6g+14=6g+14 | | 11+8-15s=19-15s | | (-3m-6)(7m+1)= | | 18b-9b+18=18+9b | | 340+4x^2-56x=25+x^2+6x | | 17-6v+18=-6v-19 | | 1/2-6/7 |

Equations solver categories